Динамічний розподіл робіт по ресурсах в неоднорідній системі з обмеженнями реального часу - Simonenko, Valery P.; Sergiyenko, Anatolij M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2016)
A method of dynamic real time scheduling of tasks in a heterogeneous system is considered. The method consists in a preliminary preparation of the initial information set, taking into account the duration of the scheduling, the complexity of tasks, as well as individual resource characteristics such as performance, memory capacity, availability of downloaded software and initial data. The algorithm of this preparation consists in forming a job time reserve matrix and performing a sequence of transformations of this matrix to the cost matrix taking into account the assignment conflict matrix. After preparation of the initial information set, the planning problem is solved by the Hungarian algorithm of finding the maximum bipartite matching.